Transcripción de la relación del viaje del licenciado Joan de Vadillo entre San Sebastián de Urabá y Cali, 1539 (2012)
ABSTRACT: This text presents the transcription of the report that judge Juan de Vadillo wrote in 1539 on his trip between San Sebastián de Urabá and Cali. This report reveals the first trip that linked these two towns and one of the first encounters between Spaniards and indigenous people of western Colombia.